KONSEP PENDIDIKAN PROFETIK PILAR HUMANISASI DALAM PEMBELAJARAN IPS - Syawaludin, Muhammad; Saliman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Education provides space for humans to improve resources to face the challenges of scientific and technological advances in today's globalization. Ideal education is not only limited to cognitive aspects but also spiritual, moral and social aspects so as to prevent character degradation in the younger generation. These aspects are listed in the humanization pillar of prophetic education which refers to efforts to make education a vehicle in fostering a balanced personality, in accordance with prophetic teachings that prioritize values, norms, spirituality, justice and concern for others. Research conducted with a qualitative approach to this literature aims to explore the concept of prophetic education humanization pillars in social studies learning. Social studies learning as part of the education curriculum offers a great opportunity to apply the concept of humanization of prophetic education. Through social studies learning, students not only learn about the structure of society and social interaction, but also understand the human values advocated by prophetic teachings. By applying this concept in social studies learning, it is hoped that educators can help students internalize the moral and ethical values needed to become citizens who contribute positively to society.